Determinants of blood glucose concentrations following a high carbohydrate meal in type 2 diabetes: A multiple linear regression analysis. (April 2023) - Xie, Cong; Jalleh, Ryan J.; Watson, Linda E.; Huang, Weikun; Sun, Yixuan; Jones, Karen L.; Horowitz, Michael; Rayner, Christopher K.; Wu, Tongzhi
Abstract: This study showed that in relatively well-controlled type 2 diabetes blood glucose levels after a high carbohydrate meal were associated positively with fasting blood glucose, but also positively with gastric emptying in the first hour and negatively with the increments in plasma glucagon-like peptide-1 (GLP-1) in the later postprandial phase.